The Eagle Cliff - Ballantyne, R. M. (Robert Michael), 1825-1894 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Eagle Cliff" by R.M. Ballantyne is a novel written in the late 19th century. The story begins with John Barret, a young man who, after an accident involving an elderly lady while cycling, embarks on an adventure that takes him and his friends on a yacht to explore the islands off the coast of Britain. The plot unfolds amidst a series of mishaps, including a fog that damages their yacht and leads them to seek refuge at an isolated residence, setting the stage for both romantic and adventurous escapades. The opening of the narrative introduces John Barret as a spirited and athletic cyclist navigating through the English countryside. His journey is abruptly altered when a collision with an elderly lady creates a wave of guilt and sets him off on an emotional spiral. Following a series of events, including a yacht disaster and the discovery of a beautiful young artist named Milly at a remote home, Barret finds himself entangled in unexpected relationships and challenges. The early chapters paint a vivid picture of his character, foreshadowing the deeper themes of courage, guilt, and the longing for adventure that will likely unfold as the story progresses. (This is an automatically generated summary.)
Release date is 2007-11-06
Produced by Nick Hodson of London, England
Keywords: Conduct of life -- Juvenile fiction; Adventure stories; Friendship -- Juvenile fiction; Natural history -- Juvenile fiction; Sailors -- Juvenile fiction; Survival skills -- Juvenile fiction; Shipwrecks -- Juvenile fiction; Outdoor life -- Juvenile fiction; Fishers -- Juvenile fiction